The effect of geographical region on the transition time of CMMI-based software process improvement / Fahad Hamed Alshammari - Alshammari, Fahad Hamed (2013)
Software Process Improvement (SPI) is one of the main contributors to the improvement of the software organization process, in terms of achieving targets on time, working within budget, and work quality. Capability Maturity Model Integration (CMMI) is one of the leading SPI models, which is based on the best practices that deal with Organization Maturity. However, despite this, the Software Engineering Institute (SEI) has identified a timeframe for achieving a particular CMMI level. Nevertheless, one of the most frequent reasons given by organizations for their reluctance in adopting CMMI, was time, whilst geographical region was deemed an independent variable that influences the relationship between process improvement and schedule deviation. Therefore, this study aims to identify the factors that affect the transition time of CMMI based SPI, during the CMMI process. It also seeks to identify the effect of Geographical Region on the transition time of CMMI. At the same time, it will propose a reference model that will assist organizations in reducing the effects of these factors, whilst accelerating the CMMI process. Interviews were used to obtain factors from software engineering process group supervisors, consultants, managers, and practitioners, of various software and service firms. A questionnaire survey was then used to identify the factors that affect the transition time of CMMI, between Malaysia and Saudi Arabia. This comparison was done using statistical analysis. Results show that Malaysian firms had different transition time factors, compared to Saudi Arabian firms (chi-square test, p < 0.05). In addition, it also shows that geographical region had a significant impact on the transition time factors of CMMI (p < α). The study produced a Transition Time Factor Implementation Framework and a Transition Time Factor Reference Model, which was validated by seven CMMI experts, from Malaysia and Saudi Arabia.